2022
DOI: 10.3390/antiox11061087
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxytyrosol Prevents Doxorubicin-Induced Oxidative Stress and Apoptosis in Cardiomyocytes

Abstract: Doxorubicin (Dox) is a highly effective chemotherapeutic agent employed in the handling of hematological and solid tumors. The effective use of Dox in cancer therapy has been seriously limited due to its well-known cardiotoxic side effects, mainly mediated by oxidative damage. Therefore, the identification of an effective and safe antagonist against Dox-induced cardiotoxicity remains a challenge. In this respect, as plant polyphenols have attracted considerable interest due to their antioxidant properties and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
1
4
0
Order By: Relevance
“…The current findings showed that the damage caused by DOX was mostly due to the production of ROS, which destroy cell walls and trigger apoptosis. Many studies confirmed our findings that DOX-induced heart damage is primarily caused by increased oxidative/nitrosative stress linked with a reduced antioxidant defense state [ 12 , 40 , 43 , 44 , 45 , 46 ]. Increased cardiac lipid peroxidation and decreased cardiac cellular GSH content in DOX-treated rats are indicators of an imbalanced redox state in the cardiomyocyte.…”
Section: Discussionsupporting
confidence: 89%
“…The current findings showed that the damage caused by DOX was mostly due to the production of ROS, which destroy cell walls and trigger apoptosis. Many studies confirmed our findings that DOX-induced heart damage is primarily caused by increased oxidative/nitrosative stress linked with a reduced antioxidant defense state [ 12 , 40 , 43 , 44 , 45 , 46 ]. Increased cardiac lipid peroxidation and decreased cardiac cellular GSH content in DOX-treated rats are indicators of an imbalanced redox state in the cardiomyocyte.…”
Section: Discussionsupporting
confidence: 89%
“…Similarly, in 143B osteosarcoma cells, OLE showed a synergistic, antiproliferative, and anti-migratory effect in combination with estradiol metabolite 2-methoxyestradiol at all OLE concentrations tested (1–250 μM for proliferation, and 100 μM for wound healing assay) [ 89 ]. On the contrary, HT did not modify doxorubicin-mediated growth inhibition of human osteosarcoma cells U-2 OS [ 277 ]. In neuroblastoma cells T98G, 277.5 μM and 555 μM OLE showed a synergistic effect with alkylating agent temozolomide on cell viability, increasing the expression of miRNAs involved in tumor growth suppression, mainly Let-7d [ 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, 50 μM and 70 μM HT reduced doxorubicin-mediated toxicity in embryonic rat cardiomyoblasts H9c2(2-1) after 48 h incubation. Also, 24 and 48 h incubation with 50 μM HT reduced doxorubicin-dependent intracellular ROS accumulation, increasing SOD2 levels and protecting cells from doxorubicin-induced apoptosis [ 277 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous antioxidants, including flavonoids and polyphenols, have been employed in the past to combat DOX-induced cardiotoxicity, according to reports. 10 In cardiac tissues intoxicated with DOX, histopathology revealed myocardial atrophy, nuclear condensation of chromosomes, and cytoplasmic vacuoles. Significant fatty blockage in the blood vessel and foamy-looking cytoplasm were cleared after DOX treatment, along with nuclear deterioration.…”
Section: Discussionmentioning
confidence: 99%